Dampak dana perimbangan terhadap pertumbuhan ekonomi dan ketimpangan antar daerah di Provinsi Jambi - Dodi Chandra; Syurya Hidayat; Rosmeli Rosmeli (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2017)
This study aims to analyze: 1) the development of balancing funds, economic growth and inequality between regions in Jambi Province; 2) the impact of balancing funds on economic growth and inequality between regions in Jambi Province. The analysis was carried out descriptively and quantitatively using regression analysis. The results of the analysis found that: 1) the average balance fund obtained by Jambi Province during 2001-2013 was Rp. 3,854,250,067, with a tendency to increase every year. The average economic growth of Jambi Province during 2001-2013 was 6.64% per year. Furthermore, the average level of inequality between regions is 0.38, which is categorized as being; 2) The balancing funds in fact have had a good impact and can trigger economic growth in Jambi Province. However, balance funds also have a negative impact on increasing inequality between regions